Demethylzeylasteral (T-96) initiates extrinsic apoptosis against prostate cancer cells by inducing ROS-mediated ER stress and suppressing autophagic flux - Yang,Dong-lin (Sociedad de Biología de Chile, 2021)
Abstract Background: Demethylzeylasteral (T-96) is a pharmacologically active triterpenoid monomer extracted from Tripterygium wilfordii Hook F (TWHF) that has been reported to exhibit anti-neoplastic effects against several types of cancer cells. However, the potential anti-tumour effects of T-96 against human Prostate cancer (CaP) cells and the possible underlying mechanisms have not been well studied. Results: In the current study, T-96 exerted significant cytotoxicity to CaP cells in vitro and induced cell cycle arrest at S-phase in a dose-dependent manner. Mechanistically, T-96 promoted the initiation of autophagy but inhibited autophagic flux by inducing ROS-mediated endoplasmic reticulum (ER) stress which subsequently activated the extrinsic apoptosis pathway in CaP cells. These findings implied that T-96-induced ER stress activated the caspase-dependent apoptosis pathway to inhibit proliferation of CaP cells. Moreover, we observed that T-96 enhances the sensitivity of CaP cells to the chemotherapeutic drug, cisplatin. Conclusions: Taken together, our data demonstrated that T-96 is a novel modulator of ER stress and autophagy, and has potential therapeutic applications against CaP in the clinic.